Growth and economic development essays in honour of A.P. Thirlwall - Arestis, Philip, 1941-; McCombie, J. S. L.; Vickerman, R. W. (Roger William); Thirlwall, A. P.; Edward Elgar Publishing (Cheltenham ; Northampton, Mass. : Edward Elgar, 2006)
This valuable and engaging new book bears eloquent testimony to A.P. Thirlwall's substantial contribution to economics over the last 40 years. The volume does not attempt to provide a comprehensive review of such a prolific figure, but rather demonstrates the considerable influence that his work on economic theory has had on his contemporaries, and the profession as a whole.
The implications of Thirlwall's law for Africa's development challenges / Mohammed Nureldin Hussain -- Thirlwall's law and Palley's pitfalls : a reconsideration / Mark Setterfield -- On specifying the demand for imports in macroeconomic models / G.C. Harcourt -- Keynes, post Keynesian analysis, and the open economies of the twenty-first century / Paul Davidson -- Cycles, aggregate demand, and growth / Miguel A. León-Ledesma -- Modelling historical growth : a contribution to the debate / Mark Roberts -- Endogenous growth theory : a partial critique / Philip Arestis and Malcolm Sawyer -- The nature of economic growth and the neoclassical approach. : more questions than answers? / John McCombie -- On the core of macroeconomic theory / John Cornwall -- The crisis of the stability pact and a proposal / Roberto Tamborini and Fernando Targetti -- Narrowing the options : the macroeconomic and financial framework for EU enlargement / Heather Gibson and Euclid Tsakalotos -- Competition and competition policy in emerging markets : international and developmental dimensions / Ajit Singh -- Models of saving, income and the macroeconomics of developing countries in the post-Keynesian tradition / Valpy FitzGerald -- The Influence of Keynes on development economics / John Toye.
Includes bibliographical references and index.
Keywords: Economic development; Development economics; Electronic books